Karakterisasi Tingkat Degradasi Superalloy Udimet 520 Pada Sudu Putar Turbin Pembangkit Listrik Tenaga Gas [Characteristic Degradation Level of Superalloy Udimet 520 of Rotating Blade of a Gas Turbine Power Plant] - Dewa Nyoman Adnyana (National Research and Innovation Agency (BRIN), 2018)
First stage rotating blades of a gas turbine power plant having design capacity of 130 MW have been in operation for more than 50.000 hours. The blade material was made of Udimet 520, a Ni- based superalloys. During its operation, the turbine blades may have been subjected to degradation due to several damage mechanisms such as thermal aging, creep, fatigue, corrosion and/or erosion. The aim of this examination was to determine the degree of degradation and the possibility of future service continuation of the turbine blades. A post-service first stage turbine blade was dismounted from the engine rotor and used for examination. Various laboratory examinations were performed including chemical analysis, metallographic examination, hardness testing and creep testing. Results of the examination obtained showed that the turbine blade material has not been experiencing some significant morphology change in microstructure due to thermal aging, either on the matrix austenite phase (g) and precipitate of gamma prime (g') or on the carbide phase particles. In addition, the level of creep resistance of the turbine blade material was still higher than the minimum creep property of the Udimet 520. Furthermore, the degree of degradation due to corrosion and/or oxidation occurred on most of the blade exterior in general was considered low. Based on this condition, the first stage gas turbine blades were considered serviceable. AbstrakSudu putar turbin tingkat pertama pada sebuah unit pembangkit listrik tenaga gas (PLTG) dengan kapasitas terpasang 130 MW telah dioperasikan selama lebih dari 50.000 jam. Menurut data desain, material sudu turbin dibuat dari paduan super berbasis Ni dengan spesifikasi Udimet 520. Selama pengoperasiannya, sudu turbin diperkirakan mengalami degradasi akibat sejumlah mekanisme kegagalan yang terjadi seperti: thermal aging, creep, fatik, korosi, dan/atau erosi. Pengujian yang dilakukan ini bertujuan untuk menentukan tingkat degradasi dan kelayakan sudu turbin untuk kelanjutan pengoperasiannya diwaktu yang akan datang. Sebuah sudu turbin tingkat pertama dilepas dari rotor unit PLTG untuk digunakan dalam pengujian ini. Sebelum melakukan pengujian, sudu turbin tersebut dibelah menjadi 2 (dua) bagian, dimana salah satu belahan diberi proses heat-treatment. Sejumlah pengujian laboratorium telah dilakukan meliputi analisa kimia, uji metalografi, uji kekerasan dan uji creep. Hasil pengujian menunjukkan bahwa material sudu turbin belum mengalami perubahan yang berarti pada morfologi struktur mikro akibat thermal aging, baik pada matrik fasa austenit (g) dan partikel/presipitat fasa gamma prime (g') Ni3 (Al,Ti) maupun pada fasa karbida. Disamping itu tingkat ketahanan creep material sudu turbin terlihat masih lebih tinggi jika dibandingkan dengan sifat ketahanan creep minimum material standar Udimet 520. Lebih jauh, tingkat degradasi akibat korosi dan/atau oksidasi yang terjadi pada permukaan luar sudu turbin pada umumnya masih tergolong rendah. Didasarkan pada kondisi tersebut, sudu turbin tingkat pertama direkomendasikan untuk dilanjutkan pemakaiannya, tetapi setelah dilakukan pekerjaan rekondisi.